Circulating microRNA-133a and its associations with left ventricular hypertrophy in men with arterial hypertension. (14th October 2021) - Koval, S; Yushko, K; Snihurska, I; Mysnychenko, O
Abstract: Introduction: Arterial hypertension (AH) is the most common cardiovascular (CV) diseases and one of the major a risk factor for CV complications and mortality. An important reason for the development and progression of a number of CV diseases are epigenetic factors regulating gene expression, which include microRNAs. MicroRNA-133a is one the epigenetics factor, which has cardioprotective properties, but its role in the development of left ventricular hypertrophy (LVH) in patients with AH, including men, is not well understood. Purpose: The aim of the study was to investigate the circulating microRNA-133a levels, its associations with left ventricular (LV) parameters and LVH in men with AH. Methods: In study was included 57 men with AH grades 2–3 aged 43 to 64. The main group consists of 32 patients with LVH and the comparison group consists of 25 patients without LVH. The main and the comparison groups were comparable in age and duration of hypertension. The control group consisted of 22 practically healthy men of comparable age. The LVH was determined according to the 2018 ESC/ESH guidelines. Circulating plasma microRNA-133a levels were obtained by polymerase chain reaction using the CFX96 Touch System, "TaqMan microRNA Assay" and "TaqMan® Universal PCR Master Mix" reagent kits. Results: In men with AH (total group) the levels of microRNA-133a were significantly lower than in practically healthy men in the control group (0.212 [0.091; 0.364]) vs (0.402 [0.178; 0.513]), p<0.05). The levels of microRNA-133a in main group were significantly lower than in comparison group and control group (0.125 [0.078; 0.295] vs 0.276 [0.126; 0.397], p<0.05 and 0.402 [0.178; 0.513]), p<0.05). In the main group (men with AH and LVH) there was a statistically significant negative correlation between microRNA-133a levels and LV mass index (R=−0.42, p<0.01) with no significant correlation with ejection fraction or E/e' (averaged) ratio (p>0.05). In men with AH of the comparison group (without LVH) there were not significant associations of microRNA-133a levels with LV parameters (p>0.05). Conclusion: The obtained results may indicate a significant role of decreased circulating plasma microRNA-133a levels in men with AH in the pathogenesis and development of the LVH. Funding Acknowledgement: Type of funding sources: None.